Poly(3, 3'''-dialkylquaterthiophene)/ZnO quantum dots based hybrid p-n junction diode - Kumar C.; Rawat G.; Kumar H.; Kumar Y.; Ratan S.; Mishra A.K.; Prakash R.; Jit S. (My University, 2025)
The organic-inorganic hybrid p-n junction diode based on poly (3,3'''-dialkylquarterthiophene) (PQT-12) and ZnO quantum dots (QDs) has been fabricated and characterized in this work. The solution process technique is used for the deposition of PQT-12 and ZnO QDs. ITO coated glass is used as substrate and bottom electrode, whereas Ag is used as a top electrode of the vertical hybrid diode. ZnO QDs facilitates the band pass photo-absorption of visible light through PQT-12 film by blocking high energy photons. The diode shows an excellent switching property with the rectification ratio of 3520 under applied bias of ±3 V. The electrical properties of the hybrid diode such as ideality factor and reverse saturation current are calculated as 3.12 and 3.5×10-s A, respectively. © 2018 IEEE.